Model Kebijakan Pengembangan Wisata Pantai Berkelanjutan Di Kota Padang, Provinsi Sumatera Barat. (JURNAL SPASIAL, 2017)
Indonesia has a natural beauty that is attractive to serve as a tourist attraction. Number of visits to both domestic and foreign travel increased by 7% per year. Padang city has four beach a tourist attraction that is Muaro Anai, Muaro Lasak, Muaro Padang and Bungus Beach. The number of tourists coming to the city of Padang increased 2.6% per year. The number of tourists visit will have an impact on the sustainability attractions. The purpose of this study to determine the level of sustainability and determine the direction of tourism development policies beach. To determine the level of sustainability attractions using multi dimention scaling (MDS). Policy directives determined using Analytical Hierarchy Process (AHP) with the involvement of experts as many as 25 people. The results of the sustainability analysis shows that attraction Muaro Padang and Muaro Lasak sustainable economic dimensions, but otherwise is not sustainable in social and ecological dimensions. Moreover, `there are two directions of policy development that is sustainable coastal attractions fostering cultural values of the community (21.4%) and building communities to take loving environment (18.7%).